2019
DOI: 10.1080/17518253.2019.1687760
|View full text |Cite
|
Sign up to set email alerts
|

Modified silica gels as recyclable adsorbents of aqueous polycyclic aromatic hydrocarbons

Abstract: Polycyclic aromatic hydrocarbons (PAHs), a class of toxic organic molecules containing multiple fused aromatic rings, are found in air, soil and water as a by-product from the incomplete combustion of organic matter. We report on the modification of silica gel using lipophilic molecules containing carboxylic acids, for anchoring to the surface via hydrogen bonds. The lipophilic component captures aqueous PAH, specifically phenanthrene, through the agency of π-π and π-sp 3 interactions. The structure-sorption-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It can be concluded that the isomerism has an influence on the aggregation behavior in the case of naphthyl-substituted alkoxysilanes. 9-PhenPhSi­(OMe) 2 shows a similar but less pronounced emission behavior like 2-NaphPhSi­(OMe) 2 with a shift to higher wavelengths typical for the phenanthrene group. , …”
Section: Results and Discussionmentioning
confidence: 87%
“…It can be concluded that the isomerism has an influence on the aggregation behavior in the case of naphthyl-substituted alkoxysilanes. 9-PhenPhSi­(OMe) 2 shows a similar but less pronounced emission behavior like 2-NaphPhSi­(OMe) 2 with a shift to higher wavelengths typical for the phenanthrene group. , …”
Section: Results and Discussionmentioning
confidence: 87%
“…In fact, to increase the adsorption efficiency of Si, its surface is often modified with hydrophobic groups to facilitate the capture of PAHs. 23 Although the use of HDPE resulted in the highest percentage of Phe retention compared to the other adsorbents, its efficiency in retaining the total amount of PAHs was lower, corresponding to only 19.4% of the total PAH emissions from the asphalt sample. For the gas−solid adsorption of the PAHs in the absence of the asphalt matrix (aqueous solution), it was possible to obtain 81.1% PAH retention with HDPE.…”
Section: Resultsmentioning
confidence: 95%
“…However, as mentioned before, the adsorption efficiency of Si is governed by the OH groups on its surface. , This probably explains the low percentage of adsorbed PAHs observed in this study. In fact, to increase the adsorption efficiency of Si, its surface is often modified with hydrophobic groups to facilitate the capture of PAHs …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations